A 4-year study of hamstring injury outcomes in elite track and field using the British Athletics rehabilitation approach. Issue 5 (14th April 2021) - Pollock, Noel; Kelly, Shane; Lee, Justin; Stone, Ben; Giakoumis, Michael; Polglass, George; Brown, James; MacDonald, Ben
Abstract : Objectives: The British Athletics Muscle Injury Classification (BAMIC) correlates with return to play in muscle injury. The aim of this study was to examine hamstring injury diagnoses and outcomes within elite track and field athletes following implementation of the British Athletics hamstring rehabilitation approach. Methods: All hamstring injuries sustained by elite track and field athletes on the British Athletics World Class Programme between December 2015 and November 2019 that underwent an MRI and had British Athletics medical team prescribed rehabilitation were included. Athlete demographics and specific injury details, including mechanism of injury, self-reported gait phase, MRI characteristics and time to return to full training (TRFT) were contemporaneously recorded. Results: 70 hamstring injuries in 46 athletes (24 women and 22 men, 24.6±3.7 years) were included. BAMIC grade and the intratendon c classification correlated with increased TRFT. Mean TRFT was 18.6 days for the entire cohort. Mean TRFT for intratendon classifications was 34±7 days (2c) and 48±17 days (3c). The overall reinjury rate was 2.9% and no reinjuries were sustained in the intratendon classifications. MRI variables of length and cross-sectional (CSA) area of muscle oedema, CSA of tendon injury and loss of tendon tension were associated with TRFT. Longitudinal length of tendon injury, in the intratendon classes, was not associated with TRFT. Conclusion: The application of BAMIC to inform hamstring rehabilitation in British Athletics results in low reinjury rates and favourable TRFT following hamstring injury. The key MRI variables associated with longer recovery are length and CSA of muscle oedema, CSA of tendon injury and loss of tendon tension.